Temporal and spatial trends of insufficient physical activity on mortality, years of life lost, and life expectancy due to noncommunicable diseases in argentina - García Witulski, Christian Martín (2022)
Fil: García-Witulski, Christian M. Pontificia Universidad Católica Argentina. Facultad de Ciencias Económicas; Argentina